Anti-CGRP monoclonal antibodies in the treatment of migraine in women: impact on menstrual relared migraine and algodysmenorrhea - Anna V. Berdnikova; Natalya B. Kadymova; Nina V. Latysheva; Margarita V. Naprienko; Elena G. Filatova (LLC "MEDIAFORMAT", 2023)
Background. Menstrual related migraine (MRM) occurs in 60% of women with migraine. These attacks are characterized by high intensity and poor response to abortive and prophylactic treatment. Hormonal therapy is one of the main treatment methods, but it has a large number of limitations. Increase in the CGRP level triggered by a decrease of estrogen levels is one of the basic mechanisms of MRM. It is of interest therefore to study the impact of anti-CGRP monoclonal antibodies (mAbs) in MRM. In addition, many patients have severe pelvic pain in the perimenstrual period (algodysmenorrhea). Algodysmenorrhea is associated with other chronic pain syndromes including migraine. Therefore, it is interesting to study the impact of anti-CGRP monoclonal antibodies on algodysmenorrhea. Material and methods. We recruited 64 women with migraine (episodic and chronic) over 18 years of age with regular menstrual cycle. 21 patients were diagnosed with MRM according to the International Classification of Headache Disorders, 3rd edition. Demographic data, migraine history, menstrual cycle characteristics and algodysmenorrhea symptoms were collected. Patients were treated with erenumab or fremanezumab for 3 months and followed up monthly with headache diaries. Results. After 3 months of treatment, the intensity of menstrual migraine attacks and algodysmenorrhea decreased by 50% or more (p=0,03* and p=0,045*, accordingly). There was a significant decrease in the total amount of headache days in MRM patients. Conclusion. Anti-CGRP mAbs are effective in MRM and algodysmenorrhea. Further studies are necessary.